Occupations and geographical distribution of mesothelioma in Switzerland 1989–2018 – record linkage of an asbestos-exposed population with the Swiss National Cohort - Locher, Benjamin N.; Barresi, Fabio; Kuhn, Barbara K.; Vrugt, Bart; Bopp, Matthias; Dressel, Holger (Swiss medical weekly, 2022)
OBJECTIVE: We investigated the possibility of linking the data of the Swiss Laboratory for Particle Analysis (Silag), a valuable but incomplete data source in the field of asbestos-related diseases, to the Swiss National Cohort (SNC). With the resulting comprehensive dataset, we intended to provide a source for further research in the field. We also conducted preliminary analyses of data focusing on occupations and regional distribution of malignant pleural mesothelioma cases. METHODS: Data of asbestos-exposed individuals available from the Silag were anonymously linked with the SNC by means of deterministic record linkage. From this linkage, data on occupation classified according to the international standard classification of occupations (ISCO) as well as the canton of residence in Switzerland could be retrieved. RESULTS: Of 838 eligible individuals from the Silag data, 788 (94.0%) could be linked to the SNC database, including 476 mesothelioma cases. In 340 cases of the latter, data on occupation and industries were available. Although the majority of them were blue-collar workers, a significant proportion (n = 44, 12.9%) had executive professions. The Canton of residence in 1990 was established in 430 of subjects with mesothelioma. A cluster could be identified in eastern Switzerland, especially in the canton of Glarus. CONCLUSIONS: It was possible to link the datasets to a large extent thereby creating a data source for further research. Of note, the linkage provided data on occupation of a selection of mesothelioma cases in Switzerland.